2016
DOI: 10.7554/elife.12977
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved studies define the nature of toxic IAPP intermediates, providing insight for anti-amyloidosis therapeutics

Abstract: Islet amyloidosis by IAPP contributes to pancreatic β-cell death in diabetes, but the nature of toxic IAPP species remains elusive. Using concurrent time-resolved biophysical and biological measurements, we define the toxic species produced during IAPP amyloid formation and link their properties to induction of rat INS-1 β-cell and murine islet toxicity. These globally flexible, low order oligomers upregulate pro-inflammatory markers and induce reactive oxygen species. They do not bind 1-anilnonaphthalene-8-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
207
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 140 publications
(225 citation statements)
references
References 100 publications
18
207
0
Order By: Relevance
“…We have shown that toxic h-IAPP LP intermediates, but not nontoxic h-IAPP amyloid fibrils, induce the production of ROS in INS-1 β cells and that this event precedes the detection of metabolic dysfunction (19). If RAGE is a mediator of h-IAPP-induced β cell toxicity, then we would expect that toxic h-IAPP LP intermediates would likewise upregulate RAGE expression before detectable loss of β cell viability.…”
Section: Rage Is Upregulated In H-iapp-induced β Cell and Islet Protementioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that toxic h-IAPP LP intermediates, but not nontoxic h-IAPP amyloid fibrils, induce the production of ROS in INS-1 β cells and that this event precedes the detection of metabolic dysfunction (19). If RAGE is a mediator of h-IAPP-induced β cell toxicity, then we would expect that toxic h-IAPP LP intermediates would likewise upregulate RAGE expression before detectable loss of β cell viability.…”
Section: Rage Is Upregulated In H-iapp-induced β Cell and Islet Protementioning
confidence: 99%
“…Amyloidogenic h-IAPP induces β cell apoptosis in vitro, in rodent models in vivo, and in human T2D (10,19,26,34,35,37,38). Multiple mechanisms of toxicity have been proposed, but there is no consensus about how h-IAPP causes β cell damage (6,17,39).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since aggregation of hIAPP progresses in vitro from monomeric through to pre-fibrillar aggregates and subsequently fibrillar forms over the course of minutes to hours (depending on the concentration and solvent used), application of freshly dissolved hIAPP to macrophages will expose these cells to a range of hIAPP aggregate species. Early, pre-fibrillar hIAPP species are the most pro-inflammatory (Masters et al 2010, Westwell-Roper et al 2011 and most toxic to INS1 cells (Abedini et al 2016). It should be noted that fibrillar hIAPP species can, however, activate the inflammasome in LPS-primed macrophages, though to a lesser extent than freshly dissolved hIAPP (Westwell-Roper et al 2016).…”
Section: Inflammatory Iapp Speciesmentioning
confidence: 99%